The Effectiveness of the Think-Pair-Project-Share (TP2S) Model in Facilitating Self Directedness of Prospective Science Teachers - Sajidan, Sajidan; Atmojo, Idam Ragil Widianto; Ardiansyah, Roy; Saputri, Dwi Yuniasih; Roslan, Roslinawati Mohd; Halim, Lilia (Jurnal Pendidikan IPA Indonesia, 2024)
Self-directedness is a crucial skill for prospective science teachers, and the Think-Pair-Project-Share (TP2S) model has shown promise in fostering collaboration and critical thinking. This aim study to investigates the effectiveness of TP2S in promoting self-directed learning among these future educators. This research aims to determine the effectiveness of the think-pair-project-share (TP2S) learning model in facilitating the self-directedness of prospective science teachers. This quantitative research uses a nonequivalent control group design. The population in this study were second semester students, while the research sample consisted of 72 students. The self-directedness data collection technique uses an instrument in the form of a scale. Based on the results of the paired sample T test, it can be seen that both experimental classes obtained a Sig value. (2-tailed) 0.000. It can be concluded that the paired sample T test value in the experimental class is 0.000<0.05 so that there is a significant difference in results between the pretest and posttest scores (H0 is rejected). It can be concluded that there is a difference in self-directedness between students who study human and environmental subjects using the think pair project share model and those who use the conventional model. It is known that the application of the TP2S learning model has an effect on the self-directedness of prospective science teachers. The implications of this research support and strengthen the results of theoretical studies that the TP2S learning model is a student-centered learning model that utilizes the ability to manage learning strategies independently.